Neuropsychology Changes in Mood Disorder - Yunias Setiawati (Departemen Ilmu Kedokteran Jiwa Fakultas Kedokteran UNAIR, 2019)
Mood and anxiety disorder are chronic neurobiologist disorder with the highest mortality and disability thet have relapsing risk social and economy burden. Etiology factor of mood disorder has not been clear yet 75% mood disorder finding at below 25 years old known as early onset bipolar with high disability and cause learning disorder at school, difficult sosialize with friends, relapsing rate and suicidal risk that higher than mood disorder caused by disorder of neurotransmitter dopamin, serotonin, GABA, glutamate, neropinephrine, and histamine. Another reserach evolve focus on relation between median prefrontal cortex (mPFC), with cortical area from amygdala, ventral sriatum, globus pollidus, medial thalamus, and ganglia basalis which related with mood disorder. Enlargement on gray matter volume and neurophsycological activity related with manic episode while volume narrowing related with depression episode, genetic factor also be assumpted have role at this disorder. Chronic psychosocial stressor will destroy cellular relisiency ad related with mood disorder. Psychological factor of mood disorder have not been yet clear untill now, while unipolar mood disorder most treated at primary helath care. Understanding of affective bipolar disorder psychopathology has benefit in early detection and intervention has purpose decreasing disability, persistent disorder and prevent relaps which will be worsening outcome.